Leadership & logology : a scriptive reading of leadership writing : a thesis presented in fulfilment of the requirements for the degree of Master of Management at Massey University - Teo-Dixon, Poh Lyn (Grace) (Massey University, 2002)
Leadership theory has developed alongside management theory since the early twentieth century. The writing of management theory has been subject to critical interpretation as evinced by 'guru' theory. In comparison, the development of leadership theory has received scant critical attention. My inquiry moves into this 'gap', explores it and then asks 'What does a critical reading of leadership writing tell us about where leadership theory is heading?' My thesis argues that leadership theory has moved from the naming of 'managers' to the designation of 'leader-managers' and in the analysis of Drucker's writing, suggests that the 'leader of leaders' has already arrived. I also highlight the multiple meanings attributed to the term 'leadership' and predict that it is becoming a 'god-term'. These observations were the result of several stages of research. Firstly, the literature on leadership indicated two trends that signalled the direction of leadership theory. One trend pointed to the rising 'image' of the manager / leader and the other to an expanding concept of leadership. Burke's theory of logology suggested that these trends were part of the nature of language which inherently tends towards hierarchical 'perfection'. In order to test Burke's theory, several of Drucker's texts were selected for analysis as they spanned more than 50 years of management and leadership writing. Applying a 'scriptive' approach to reading and critically analysing Drucker's texts, I traced the development of the manager/leader and the concept of leadership. I also discovered the concept of knowledge is closely aligned with leadership. In the final analysis, I acknowledged the alternative perspective logology brings to leadership theory and anticipate the exciting possibilities for further research such a perspective provides.
Keywords: Leadership; Leadership theory; Management theory